The Relationship Of Knowledge, Education, And Family Support With The Iva Examination In The Working Area Of The Sido Mulyo Health Center, Banyuasin Regency In 2021 - Baidah; Satra Yunola; Turiyani (Institute of Computer Science (IOCS), 2022)
Cervical cancer is most often experienced by women with an estimated 570.00 new cases in 2018. Representing 6.6% of all female cancers, approximately 90% of deaths from cervical cancer occur in low-and middle-income countries (WHO,2018 ).The purpose of this study was to determine the relationship between knowledge, education and family support with IVA examination in the working area of ​​sido mulyo public health center, Banyuasin regency in 2021. This type of research was Qualitative using anAnalytical Survey with a Cross-Sectional approach. The population in this study were women of childbearing age (WUS) as many as 693 respondents and with a total sample of 70 respondents. The data analysis was carried out in two stages namely univariate and bivariate analysis with Chi-Square statistical test. The result of the study found that there was a relationship between knowledge ( p-value = 0.048), education (p-value=0.002) and family support (p-value=0.047) with IVAexamination in the work area of ​​the sido mulyo health center, Banyuasin regency in 2021.It is hoped can be an illustration of the health center to be able to further improve counseling or provide information to WUS.